Extraction and purification of beta-amylase from stems of Abrus precatorius by three phase partitioning. (15th September 2015) - Sagu, Sorel Tchewonpi; Nso, Emmanuel Jong; Homann, Thomas; Kapseu, César; Rawel, Harshadrai M.
Highlights: Stems of Abrus precatorius were used for the first time to extract a beta-amylase. Amylase was purified by three phase partitioning and optimized by Doehlert design. HPLC of hydrolysis products allows to identify and characterize a beta-amylase. Unidentified high molecular weight protease was detected. Abstract: The stems of Abrus precatorius were used to extract a beta-amylase enriched fraction. A three phase partitioning method and a Doehlert design with 3 variables (ratio of crude extract/ t -butanol, the ammonium sulphate saturation and pH) were used. The data was fitted in a second-order polynomial model and the parameters were optimized to enrich beta-amylase. Experimental responses for the modulation were recovery of activity and the purification factor. The optimal conditions were: a ratio of crude extract/ t -butanol of 0.87 (v/v), saturation in ammonium sulphate of 49.46% (w/v) and a pH of 5.2. An activity recovery of 156.2% and a purification factor of 10.17 were found. The enriched enzyme was identified as a beta-amylase and its molecular weight was 60.1 kDa. K m and V max values were 79.37 mg/ml and 5.13 U/ml, respectively and the highest activity was registered at a temperature of 70 °C and a pH between 6 and 6.5. A significant stabilization of the beta-amylase was observed up to 65 °C.